2015
DOI: 10.1371/journal.pone.0128432
|View full text |Cite
|
Sign up to set email alerts
|

MiR-335 Regulates Hif-1α to Reduce Cell Death in Both Mouse Cell Line and Rat Ischemic Models

Abstract: Hypoxia inducible factor-1α facilitates cellular adaptation to hypoxic conditions. Hence its tight regulation is crucial in hypoxia related diseases such as cerebral ischemia. Changes in hypoxia inducible factor-1α expression upon cerebral ischemia influence the expression of its downstream genes which eventually determines the extent of cellular damage. MicroRNAs are endogenous regulators of gene expression that have rapidly emerged as promising therapeutic targets in several diseases. In this study, we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 64 publications
1
42
0
1
Order By: Relevance
“…We found that the expression of miR-140-5p to be increased in IFG as well as in T2DM, in both the human and rat miRNA microarray analyses, as well as in our in vitro study, where miR-140-5p level increased with increasing glucose concentrations ( Table 1 and Table S2 [ 72 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 ]). This increase was also found to correlate with the increase in apoptosis ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the expression of miR-140-5p to be increased in IFG as well as in T2DM, in both the human and rat miRNA microarray analyses, as well as in our in vitro study, where miR-140-5p level increased with increasing glucose concentrations ( Table 1 and Table S2 [ 72 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 ]). This increase was also found to correlate with the increase in apoptosis ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Post hoc test was performed with Bonferroni correction to determine the difference between the different groups. Hierarchical clustering (HCL) and k-means clustering were performed using TIGR MeV (TMeV) software and Partek ® Genomics Suite™ 6.6 Software [ 133 , 134 ].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, overexpression of miR-210 has been found to be associated with angiogenesis in the brain of adult non ischemic mice with an up-regulation of VEGF [ 50 ]. In a rat model of middle cerebral artery occlusion, miR-139 and miR-335 were found to be down-regulated in the endothelial cells [ 51 , 52 ]. Both miR-139 and miR-335 are closely associated with stroke-induced angiogenesis via ROCK1 and ROCK2 signalling (both ROCK1 and ROCK2 are VEGF signalling regulators) [ 49 ].…”
Section: Angiogenesis and Strokementioning
confidence: 99%
“…A number of studies have focused on regulatory factors that target HIF-1α. For example, microRNA-18a (miR-18a) has been observed to regulate the expression of HIF-1α in certain tumor tissues (7)(8)(9). However, to the best of our knowledge, the effects of miR-18a on HIF-1α expression in invasive meningiomas has not previously been reported.…”
Section: Introductionmentioning
confidence: 98%